Analisis Komparatif Prevalence of Undernourishment dan Kualitas Pangan pada Provinsi di Indonesia Sebelum dan Selama COVID-19 (2019–2021): Comparative Analysis of Prevalence of Undernourishment and Dietary Quality in Indonesian Provinces Before and During COVID-19 (2019-2021) - Rahayu Sutrisno; Nia Novita Wirawan; Widya Rahmawati; Irka Dwi Fatmawati (Amerta Nutrition, 2025)
Background: The COVID-19 pandemic disrupted global food systems, including those in Indonesia. However, evidence at the provincial level remains limited, despite the importance of regional variation in shaping vulnerability and recovery capacity. Objectives: This study examined changes in the Prevalence of Undernourishment (PoU), dietary quality assessed through Desirable Dietary Pattern (DDP) scores, energy and protein availability and consumption, and provincial recovery capacity using the Recovery Gap Index (RGI) before (2019) and during the pandemic (2020-2021). Methods: A quantitative study was conducted using secondary data from 34 provinces obtained from the National Food Agency for the period 2019-2021. Consumption variables were analyzed using RM-ANOVA, and PoU and availability indicators were tested using the Friedman test with Wilcoxon post-hoc comparisons. RGI was calculated as the difference between 2021 and 2019 values. Significance was set at p-value<0.05. Results: PoU increased significantly across years (p-value<0.001). DDP availability score differed between years (p-value=0.009), although the difference between 2020 and 2021 became non-significant after correction. DDP consumption score, availability of energy and protein, and protein intake remained stable (p-value>0.05). Energy consumption increased significantly from 2020 to 2021 (+29.7 kcal/capita/day; p-value=0.010). RGI showed that 32% to 74% of provinces experienced deterioration relative to pre-pandemic levels, especially for PoU. Conclusions: The COVID-19 pandemic increased PoU indicators and reduced dietary quality. Although energy consumption improved, recovery was uneven across provinces. These findings indicate the need for policies to strengthen PoU and dietary quality tailored to provincial contexts to reduce interregional disparities.